Battery Operated USG Applicator - Ahmed, MR; Billah, MM; Ziauddin, ATM (Progressive Agriculture, 2013)
Nowadays USG application in paddy field is an innovative technology to reduce the nitrogen fertilizer losses in the field. Manual application of USG in the field by hand between four seedlings is very much time consuming, costly and back breaking task. As a result different models of USG applicator were developed in home and abroad. Most of the applicators are manually pushed or pull type. An applicator was designed and developed to operate by a DC electric motor. In this machine 12 Volt 9 AH rechargeable battery was used. Power was transmitted by pulley and v-belt from the motor to the driven wheel. The average missing rate was found 4.84% and the average applicator capacity was found 19.37 kg/hr and the average field capacity was found 0.0924 ha/hr. When the machine operated in the unpuddled land, distance between two dropped guti was found averagely 38.76 cm. By selecting more powerful motor, the machine performance can be improved. DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16618 Progress. Agric. 23(1 & 2): 75 80, 2012